2018
DOI: 10.1155/2018/1298087
|View full text |Cite
|
Sign up to set email alerts
|

Depth and Lineament Maps Derived from North Cameroon Gravity Data Computed by Artificial Neural Network

Abstract: Accurate interpretation of geological structures inverted from gravity data is highly dependent on the coverage of the recorded gravity data. In this work, Artificial Neural Networks (ANNs) are implemented using Levenberg-Marquardt algorithm (LMA) to construct a background density model for predicting gravity data across Northern Cameroon and its surroundings. This approach yields statistical predictions of gravity values (low values of errors) with 97.48%, 0.10, and 0.89, respectively, for correlation, Mean B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Mouzong et al [39] presented a novel approach for constructing a background density model for predicting gravity data in Northern Cameroon and its surroundings using artificial neural networks (ANN) with the Levenberg-Marquardt algorithm. The study found that this approach yielded highly accurate statistical predictions of gravity values with low error.…”
Section: Global and Regional Trends In Geothermal Energymentioning
confidence: 99%
“…Mouzong et al [39] presented a novel approach for constructing a background density model for predicting gravity data in Northern Cameroon and its surroundings using artificial neural networks (ANN) with the Levenberg-Marquardt algorithm. The study found that this approach yielded highly accurate statistical predictions of gravity values with low error.…”
Section: Global and Regional Trends In Geothermal Energymentioning
confidence: 99%